Development and characterization of thermoplastic sugar palm starch/agar polymer blend, reinforced seaweed waste and sugar palm fiber hybrid composite - Jumaidin, Ridhwan (2017)
In recent, the needs to develop more environmental friendly product is increasing due to the accumulating of non-biodegradable waste, particularly the disposable product. Hence, various kinds of more environmental friendly materials were developed in order to tackle this issue. Biopolymer derived from renewable resources is a promising alternative material for petroleum based polymer since it is readily biodegradable and thus, more environmental friendly. Among the biopolymer, starch is one of the most promising due to the easy availability, low cost, abundant in nature, renewable, and biodegradable. Sugar palm is a versatile plant that is regarded as renewable source for fibre and starch. However, the inborn deterrent associated with the biopolymer derived from sugar palm starch (SPS) such as the poor mechanical properties has limits its potential applications. Meanwhile, Eucheuma cottonii seaweed is a resourceful macro alga which is massively cultivated for the production of its hydrocolloids, namely carrageenan. However, due to the relatively low carrageenan content in the raw seaweed, huge amount of solid wastes were produced during processing which is yet to be utilized. Hence, characterizations of the seaweed wastes were carried out to analyse its potential as reinforcement material. Then, several modification methods were employed to enhance the properties of thermoplastic SPS i. e; (1) blending thermoplastic SPS with agar polymer (2) reinforcement of thermoplastic SPS/agar (TPSA) blend with seaweed wastes, and (3) hybridization of seaweed wastes with sugar palm fibre in the TPSA composites. Consequently, thermoplastic SPS/agar blends were successfully developed by using melt-mixing and compression moulding method. The findings show that the tensile, flexural, and impact properties of the material were improved following the incorporation of agar. The thermal properties of the material were slightly improved as the agar content increased from 0 to 40 wt%. In terms of physical properties, the addition of agar has increased the water affinity characteristics of the polymer blend. Furthermore, the influence of seaweed wastes at varying content (0 to 40 wt%) on the mechanical, thermal, physical, and biodegradation characteristics of TPSA were investigated. Improvement in the tensile, flexural, and impact properties of the composites were evidence after incorporation of seaweed waste. It also evident from the thermogravimetric analysis (TGA) results that the thermal stability of the composites were enhanced with addition of seaweed waste. In terms of the physical properties, addition of seaweed has led to higher water affinity of the composites. After soil burial for 2 and 4 weeks, the biodegradation of the composites were enhanced with the incorporation of seaweed waste. Lastly, the effects of sugar palm fibre hybridization with seaweed/TPSA composites were evaluated. Hybridized seaweed waste/SPF reinforcement at weight ratio of 0:100, 25:75, 50:50, 75:25, and 100:0 were prepared by using TPSA polymer blend as the matrix. Obtained results indicated that hybrid composites display improved tensile and flexural properties accompanied with lower impact resistance. Thermal stability of the hybrid composites were enhanced than the individual seaweed waste composite. Water absorption, thickness swelling, water solubility, and soil burial tests showed higher water and biodegradation resistance of the hybrid composites. Overall, the findings from the current study demonstrated that thermoplastic SPS modified by agar, seaweed wastes, and hybridization with SPF has shown improved functional characteristics than the origin material. In conclusion, the TPSA polymer blend reinforced seaweed waste/SPF hybrid composites are potential alternative material for biodegradable product i. e disposable tray with enhanced properties.